2013
DOI: 10.1111/hepr.12007
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic computed tomography appearance of tumor response after stereotactic body radiation therapy for hepatocellular carcinoma: How should we evaluate treatment effects?

Abstract: The dynamic CT appearance after SBRT for HCC was classified into four types. Residual early arterial enhancement disappeared within 6 months in most type 3 cases; therefore, early assessment within 3 months may result in a misleading response evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 14 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…This finding is not entirely surprising on the basis of prior experiences with neoplasms undergoing SBRT in other sites in the body [24, 41]. However, this finding indicates that an adjustment in the interpretation of posttreatment imaging studies is required because persistent enhancement after surgical resection or ablative therapy (e.g., radiotherapy, cryotherapy) would be normally considered as a sign of treatment failure.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This finding is not entirely surprising on the basis of prior experiences with neoplasms undergoing SBRT in other sites in the body [24, 41]. However, this finding indicates that an adjustment in the interpretation of posttreatment imaging studies is required because persistent enhancement after surgical resection or ablative therapy (e.g., radiotherapy, cryotherapy) would be normally considered as a sign of treatment failure.…”
Section: Discussionmentioning
confidence: 80%
“…However, these criteria may not be applicable to assess response to SBRT. For example, persistent enhancement is observed in vestibular schwannomas successfully treated with SBRT [23], and early enhancement may be observed in hepatocellular carcinomas after treatment with SBRT [24]. …”
mentioning
confidence: 99%
“…The dynamic CT appearance of tumor response after SBRT is also various [9], and it is sometime difficult to distinguish from the CT appearance of normal liver injury. This study suggested that it will be useful to understand these various imaging patterns of normal liver injury for evaluation of tumor response after SBRT.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the relationship between the change in CT appearance over time following SBRT and related factors or adverse effects. We have also observed that the CT appearance of tumor response following SBRT differs from that following conventional radiotherapy [9]; however, we focused on normal or cirrhotic liver injury in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…The Model for End‐Stage Liver Disease (MELD)‐Na score was calculated as described by Kim et al . Details of the inclusion criteria for SBRT and treatment procedure have been described previously . The summary of treatment procedure was as follows.…”
Section: Case Reportsmentioning
confidence: 99%